Foliar-feeding insects acquire microbiomes from the soil rather than the host plant - S. Emilia Hannula (Nature Portfolio, 2019)
Leaf-feeding insect microbiomes could be influenced by the soil, the plant, or a product of the two. Here, the authors conduct a series of experiments to show that an herbivorous insect predominantly acquires its microbiome from the soil rather than the plant, and that these insect microbiomes reflect soil legacies of earlier growing plants.